Toll-like receptors targeting technology for the treatment of lymphoma. (1st November 2016) - Batool, Maria; Anwar, Muhammad Ayaz; Choi, Sangdun
ABSTRACT: Introduction: The crucial role of Toll-like Receptors (TLRs) in innate and adaptive immune systems is well discussed in the literature. In cancer, TLRs act as a double-edged sword that can promote or suppress tumor growth. Areas covered: In this article, the authors uncover the potential role of TLRs in lymphomas, which are cancers related to the lymphatic system and blood cells. TLRs are de facto inflammation-inducing receptors that can either worsen disease or ameliorate lymphoma treatment. From this perspective, the usage of TLRs to modulate the immune system toward lymphoma regression is desirable. Various strategies have been used so far, and novel ways are being sought out to cure lymphoma. Expert opinion: TLR ligands have successfully been used to improve patient health; however, these receptors must be finely tuned to further optimize therapy. For a better outcome, novel specific ligands, improved pharmacodynamics, and unique targets should be discerned. Ligands with conjugated molecules, nanoparticles, and targeted drug delivery can highly optimize the therapy for lymphoma with various etiologies.